NutritionCalc plus[Cakerapadat] - Silveroaks Communication (New York : McGraw-Hill, 2009)
NutritionCalc Plus 3.2 is a suite of powerful self-assessment tools that allow you to monitor your personal diet and health goals. An imporved interface and the realibility of the ESHA database make NutritionCalc Plus 3.2 your best choice for diet analysis software
System requirement: Microsoft Windows XP, Microsoft Vista; 1Ghz processor or faster recommended; 1GB of system memory; 100MB free disk space; 8x or faster CD-ROM drive